IMPLEMENTASI KETERAMPILAN DIGITALISASI BAGI GURU TERHADAP KOMPETENSI PENGEMBANGAN MEDIA DAN BAHAN AJAR DI RA AL KAMILAH: Studi Kasus di Ra Al Kamilah Kecamatan Selaawi Garut - Dede Rini; Universitas Panca Sakti (LPPM Universitas Bina Bangsa, 2022)
The use of information and communication technology (ICT) in teaching and learning process (PBM) is currently one of the alternatives in the learning process. ICT-based teaching materials are becoming more interactive means of explaining a material. With ICT developed learning materials equipped with multimedia facilities, so that its presentation can be more interesting and the material can be depicted visually so that the presentation of the material can be equipped with pictures, video and animation. Currently, there are many online media platforms that can be used in learning, one of which is YouTube. YouTube is a social media or video sharing website where there are several categories in video groupings such as entertainment, sports, education, and so on. By utilizing this YouTube application as a learning medium, it can improve the quality of learning